PERANAN PENINGKATAN IRIGASI DENGAN POMPANISASI AIR SUNGAI TERHADAP PRODUKTIVITAS LAHAN, KESEMPATAN KERJA DAN PENDAPATAN PETANI / DIKABUPATEN WONOGIRI - Sutarno FP UTP Ska (JURNAL ILMIAH AGRINECA)
Research on the role of an irrigation increase with a pumping of river water on the productivities of farmers’ field, job opportunity and income in Wonogiri Regency aims at knowing the influence of the irrigation increase on the use of the inputs of agriculture, the field productivity, the job opportunity and the distribution of farmer’s income. The irrigation increase increases the use of total inputs as many as 88.9% and the worker as many as 65%. The irrigation increase influences actually in increasing the agricultural income as many as 127.8%. By the irrigation increase, it causes a medium unevenness. 40% of farmers with low income only enjoy 15.8% of the total incomes, while the areas without an irrigation enjoy 17.3% of the total incomes of agriculture.